Optimizing Concrete Mattress Fabrication Through Lean Project Management: A Value Stream Mapping Approach to Lead Time Reduction - Supriyadi, Supriyadi; Nugroho, Wahyu (Universitas Serang Raya, 2025)
This study aims to minimize waste in the Fabrication Service of Concrete Mattress project and provide control recommendations to minimize delays in the project. This study uses the Lean method and the Critical Chain Project Management (CCPM) method, where the Lean method is used to identify waste with tools such as Work Breakdown Structure, Value Stream Mapping (VSM), Value Stream Analysis Tool (Valsat), Root Cause Analysis (RCA), and Risk Matrix. Meanwhile, Critical Chain Project Management is used to control project time to prevent delays. The results of the study obtained a Lead Time of 89 days with a Process Cycle Efficiency (PCE) value of 65.17%. To identify the factors causing waste, RCA and risk management analyses were conducted. The cause of critical waste was the formwork dismantling method, which fell into the extreme category. The first alternative was to change the formwork dismantling process by using wheels and 150x75 C-channels as rails, which would reduce the time needed to dismantle and reassemble the formwork. The second alternative is to provide buffer time using the Critical Chain Project Management (CCPM) method. After scheduling with CCPM, a time acceleration of 10 days was achieved, from the initial lead time of 89 days to 79 days with a buffer of 10 days, with a PCE value of 73.42%. There was an increase in process effectiveness of 8.25%.